Pore-water data of surface sediments retrieved from two fjords in South Georgia, sub-Antarctica - Berenice Ebner; Susann Henkel; Peter Kraal; Daniel Müller; Male Köster; Michael Staubwasser; Katja Laufer-Meiser; Laura Kattein; Walter Geibert; Sabine Kasten (PANGAEA, 2025)
During the PS133/2 research cruise with the German research vessel RV Polarstern in the austral summer of November and December 2022 into the Southern Ocean, sediment samples were collected using a multicorer at five stations and a handheld gravity corer (UWITEC) from a zodiac at two additional stations across two fjords in South Georgia: King Haakon Bay and Cumberland Bay. The main objective was to determine and quantify the different sources and transport pathways of iron from two fjords of South Georgia into the open ocean. The MUC cores were sliced into 1-2 cm segments down to a maximum depth of 30 cm. Adjacent sediment cores were cut at the same depth resolution. Pore-water analyses were conducted for nitrite (NO2-), nitrate (NO3-), silicate (SiO2), phosphate (PO4^3-), ammonium (NH4+), dissolved inorganic carbon (DIC), chloride (Cl-), sulfate (SO42-), hydrogen sulfide (H2S), alkalinity, dissolved Fe (dFe) and dissolved manganese (dMn). Surface sediment pore-water samples were analyzed for their iron isotopic composition (δ56Fe) at 6 stations
In: Ebner, B et al. (2025): Oxygen profiles, pore-water- and solid phase data of surface sediments retrieved from two fjords in South Georgia, sub-Antarctica [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.986658